Role of the HIPPO pathway as potential key player in the cross talk between oncology and cardiology. (March 2021) - Manno, Girolamo; Filorizzo, Clarissa; Fanale, Daniele; Brando, Chiara; Di Lisi, Daniela; Lunetta, Monica; Bazan, Viviana; Russo, Antonio; Novo, Giuseppina
Highlights: YAP/TAZ are the main regulator of organ growth and proliferation. They are essential for cancer initiation, tumorigenesis, progression and metastasis. They are fundamental in heart development, proliferation and size regulation. Abstract: The HIPPO pathway (HP) is a highly conserved kinase cascade that affects organ size by regulating proliferation, cell survival and differentiation. Discovered in Drosophila melanogaster to early 2000, it immediately opened wide frontiers in the field of research. Over the last years the field of knowledge on HP is quickly expanding and it is thought will offer many answers on complex pathologies. Here, we summarized the results of several studies that have investigated HP signaling both in oncology than in cardiology field, with an overview on future perspectives in cardiology research.